2007
DOI: 10.1002/ijc.23343
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and cancer: Profile, profile, profile

Abstract: MicroRNAs (miRNAs) represent a new class of small noncoding RNAs (ncRNAs, RNAs that do not codify for proteins) that can regulate gene expression by targeting messenger RNAs of protein coding genes and other ncRNA transcripts. miRNAs were recently found to be involved in the pathophysiology of all types of analyzed human cancers mainly by aberrant gene expression. This is characterized by abnormal levels of expression for mature and/or precursor miRNA transcripts in comparison to the corresponding normal tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
140
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(145 citation statements)
references
References 80 publications
1
140
0
4
Order By: Relevance
“…On the other hand, our data and others [25,27,28,[54][55][56][57][58][59][60][61][62][63][64][65][66] have shown that quantitative changes in the expression of few miRNA genes in stool or blood that are associated with colon cancer permit development of more sensitive and specific CRC molecular markers than those currently available on the market. In comparison to the commonly employed FOBT stool test, a noninvasive molecular and reliable test would particularly be more convenient as there would be no requirement for dietary restriction, or meticulous collection of samples, and thus a screening test would be acceptable to a broader segment of the population.…”
Section: Current Methods For Colon Cancer Screeningmentioning
confidence: 55%
See 2 more Smart Citations
“…On the other hand, our data and others [25,27,28,[54][55][56][57][58][59][60][61][62][63][64][65][66] have shown that quantitative changes in the expression of few miRNA genes in stool or blood that are associated with colon cancer permit development of more sensitive and specific CRC molecular markers than those currently available on the market. In comparison to the commonly employed FOBT stool test, a noninvasive molecular and reliable test would particularly be more convenient as there would be no requirement for dietary restriction, or meticulous collection of samples, and thus a screening test would be acceptable to a broader segment of the population.…”
Section: Current Methods For Colon Cancer Screeningmentioning
confidence: 55%
“…It should be emphasized that although not all of the shed cells in stool are derived from a tumor, data published by us and others [25,27,28,[56][57][58][59][60][61][62][63][64][65][66][67][68] have indicate that diagnostic miRNA gene expression profiles are associated with adequate number of exfoliated cancerous cells and enough transformed RNA is released in the stool, and also the availability of measurable amount of circulating. miRNA genes in blood (either cellular or extracellularly), which can be determined quantitatively by a sensitive technique such as PCR in spite of the presence of bacterial DNA, non-transformed RNA and other interfering substances.…”
Section: Current Methods For Colon Cancer Screeningmentioning
confidence: 98%
See 1 more Smart Citation
“…5,14 In fact, UCRs are even more conserved than coding genes are, and UCRs are now believed to have fundamental functions in vertebrate evolution, including that of mammals. 2,[14][15][16] UCRs are frequently found in fragile genomic regions that are usually associated with cancer, and UCG expression is aberrant in several human carcinomas and leukemias compared to that of their normal tissue counterparts. 12 Deregulated UCG signatures are cancer specific and have prognostic implications.…”
Section: Hotair and Ultraconserved Regions (Ucrs)mentioning
confidence: 99%
“…4,5 miRNAs regulate the expression of roughly 10-30% of all human genes through post-transcriptional mechanisms and their abnormal expression have been linked with many human diseases including cancer. 6,7 Various single nucleotide polymorphisms (SNPs) are known to exist in miRNA genes, which can lead to variations in the quantity of miRNAs resulting in diverse functional consequences and, therefore, may represent ideal candidate biomarkers for cancer prognosis. 8 Various genetic association studies have explored the function of pre-miRNA polymorphisms in cancers including non-small cell lung cancer (NSCLC), 9 breast cancer, 10 hepatocellular carcinoma, 11 bladder cancer 12 and papillary thyroid carcinoma.…”
Section: Introductionmentioning
confidence: 99%